2022
DOI: 10.1186/s12870-022-03507-x
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress tolerance of the intertidal red alga Neoporphyra haitanensis

Abstract: Background Red algae Porphyra sensu lato grow naturally in the unfavorable intertidal environment, in which they are exposed to substantial temperature fluctuations. The strategies of Porphyra to tolerate cold stress are poorly understood. Results Herein, investigations revealed that chilling and freezing induced alterations in the physiological properties, gene transcriptional profiles and metabolite levels in the economically important red algae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The findings also showed that, environmental factors such as temperature and salinity have a limiting effect on algal biomass in the presence of growth inhibitors (ABA) and growth stimulants (IAA). Zhu et al (2022) found that, the IAA level accompanied by some other growth regulatory phytohormones in red algae, Neoporphyra haitanensis, decrease significantly upon exposing to cold temperature, representing that algae could adjust to the cold stress by their regulating phytohormones and slowing down growth subsequently. Though, some other phytohormones related to stress resistance, such as ABA, were expressively increase at low temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…The findings also showed that, environmental factors such as temperature and salinity have a limiting effect on algal biomass in the presence of growth inhibitors (ABA) and growth stimulants (IAA). Zhu et al (2022) found that, the IAA level accompanied by some other growth regulatory phytohormones in red algae, Neoporphyra haitanensis, decrease significantly upon exposing to cold temperature, representing that algae could adjust to the cold stress by their regulating phytohormones and slowing down growth subsequently. Though, some other phytohormones related to stress resistance, such as ABA, were expressively increase at low temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…Higher content of inositol was observed in high temperature (28°C), which suggested that inositol may function as a compatible solute for protection against high temperature (Tan et al, 2013). The accumulation of floridoside and isofloridoside can effectively stabilize the macromolecular substances and membrane structures in cells at low and high temperatures, preventing them from being damaged by cold or high stress (Liang et al, 2021; Zhu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Pyropia must have already developed a variety of highly effective strategies and mechanisms to overcome these environmental stresses. Most physiological studies of Pyropia have concentrated on responses to temperature of thalli (Chen et al, 2016; Luo et al, 2014; Wang et al, 2018; Wu et al, 2022; Zhu et al, 2022). The growth rates, photosynthetic performances, and photosynthetic pigment concentrations increased with increasing temperature, but decreased when the temperature increased at the thermal threshold of Pyropia haitanensis (24°C) (Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cold snaps are also predicted to increase, and may have large impacts on intertidal species in polar and subpolar systems (Becker et al 2009, Scrosati andEllrich 2018). Cold snaps during the shoulder seasons when frosts and sea ice can occur earlier or later in the season can result in extracellular ice formation leading to cell death and inhibition to growth and development (Davison et al 1989, Zhu et al 2022. It is, therefore, necessary to investigate seaweed tolerance to both extreme heat and cold, to understand global patterns and drivers of seaweed losses and to be able to predict the future vulnerability of these important habitats.…”
mentioning
confidence: 99%